Hubungan Frekuensi Penggunaan Bahasa Daerah Dengan Kemampuan Menulis Teks Fabel Siswa Kelas VII SMP Negeri 1 Tigalingga - Yolanda Ginting (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to describe the relationship between the frequency of use of regional languages and the ability to write fable texts for class VII students at SMP Negeri 1 Tigalingga. The population of this study was all class VII students of SMP Negeri 1 Tigalingga with a total of 311 people. Sample determination was carried out using simple random sampling. The method used in this research is correlational research. The instruments used are questionnaires and tests. The average score obtained by students through distributing questionnaires was 71.41 and the average score in writing fable texts was 71.58. The results of data analysis in proposing a hypothesis show that tcount is 5.06, then look at the significance level α = 0.05 with df= n-k = 34-1 = 33, and obtain ttable 1.69. So it can be concluded that tcount is greater than ttable, namely 5.06 is greater than 1.69. Thus the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a relationship between the frequency of use of regional languages and students' ability to write fable texts.